Analysis of Speed Limiting Using Speed Cameras: Case Study in Indonesian Toll Road - Patriot, Teguh; Kusuma, Andyka; Nahry, Nahry (Universitas Indonesia, 2020)
Indonesian Police attempt to reduce the fatality rate of traffic accidents by enforcing the law on speed restrictions using speed cameras. The National Police Traffic Corps (Korlantas), from 2017 to 2018, had installed 75 units of speed cameras along Jakarta Toll Roads including Cikampek, Jagorawi, Bitung, and many others. By the end of 2020, Korlantas is expected to install 75 more units on the arterial roads of Jakarta. This study aims to analyze the implementation of vehicle speed deceleration through signs and speed cameras in the control zone. The data analyzed by comparing the speed of vehicles when crossing the control zone using the normal distribution Z test, with a 5% margin of error. The research shows that speed deceleration policy using signs and speed cameras in the control zone reduces the speed by 9% or equal to an average speed of 8 km/hour. Drivers who obeyed the speed limit reach 76.6% or 230 vehicles from 302 vehicle samples, where most of them are buses, followed by passenger cars and freight cars, respectively. The application of speed deceleration using signs and speed cameras in the toll toad meets the planning target and is recommended to be implemented across the country.